Length and repeat-sequence variation in 58 STRs and 94 SNPs in two Spanish populations - Casals, Ferran; Anglada, Roger; Bonet, Núria; Rasal, Raquel; van der Gaag, Kristiaan J.; Hoogenboom, Jerry; Solé-Morata, Neus; Comas, David; Calafell, Francesc (Forensic science international : genetics, 2017)
•We genotyped the Illumina ForenSeq™ Primer Mix A in 88 Spanish Roma and 143 Catalans.•The repeat region sequence is much more informative than allele length for many loci.•Overall informativeness is extremely high.•A systematic yet concise nomenclature for sequence-based alleles is needed. We have genotyped the 58 STRs (27 autosomal, 24 Y-STRs and 7 X-STRs) and 94 autosomal SNPs in Illumina ForenSeq™ Primer Mix A in 88 Spanish Roma (Gypsy) samples and 143 Catalans. Since this platform is based in massive parallel sequencing, we have used simple R scripts to uncover the sequence variation in the repeat region. Thus, we have found, across 58 STRs, 541 length-based alleles, which, after considering repeat-sequence variation, became 804 different alleles. All loci in both populations were in Hardy-Weinberg equilibrium. FST between both populations was 0.0178 for autosomal SNPs, 0.0146 for autosomal STRs, 0.0101 for X-STRs and 0.1866 for Y-STRs. Combined a priori statistics showed quite large; for instance, pooling all the autosomal loci, the a priori probabilities of discriminating a suspect become 1−(2.3×10−70) and 1−(5.9×10−73), for Roma and Catalans respectively, and the chances of excluding a false father in a trio are 1−(2.6×10−20) and 1−(2.0×10−21).